Psychoeducation through SEKOPER (Women's School) Increases Knowledge of Stunting in Mothers - Zuliani, Zuliani; Retnowuni, Arifa; Masruroh, Masruroh; Yudianto, Andi; Ulfa, Ana Farida; Yani, Athi' Linda; Qomariana, Anna; Ninuk, Devin Prihan; Lestari, Trijati Puspita (Universitas Muhammadiyah Lamongan, 2023)
Introduction: Women have strategic roles that need to be activated and optimized in order to be integrated in development. But to achieve that, women are still faced with various diverse problems, especially in the scope of gender. Stunting is one of the most important global problems that has not been addressed in Indonesia. Family empowerment efforts are also very necessary. In overcoming the problem of stunting. This research aims to analyze women's knowledge about stunting through SEKOPER (women's school) after being given educationMethod: This research method is experimental with a one group pre test-post test design approach. The population is mothers who have children under 60 months of age who are given education about stunting. The sampling technique used simple random sampling with 27 respondents. The instrument uses a questionnaire with data collection carried out twice for pre and post values. Data analysis used Wilcoxon rank.Results: The results show that most of the respondents' knowledge before psychoeducation was sufficient and afterwards most of them had good knowledge. Obtained p value = 0.000 which shows that there is a difference in mean knowledge before and after being given psychoeducation.Conclusion: Psychoeducation has an impact on knowledge and efforts to prevent stunting. It is hoped that preventive efforts in the community can be carried out optimally and sustainably.Keywords: Women, Psicoeducation, Stunting, Suitcase